Around otherness: paradigms and behaviors (2014)
This is a reflection on the problems of the other one, the different in situation of social subordination, victim of human rights violations. From a multicultural perspective, it advocates respect for the other and denounces how as a result of the closure of borders, there have been numerous incidents where migrants die drowned or in other circumstances.